If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = 3 + -9x Solving -24 = 3 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -24 + 9x = 3 + -9x + 9x Combine like terms: -9x + 9x = 0 -24 + 9x = 3 + 0 -24 + 9x = 3 Add '24' to each side of the equation. -24 + 24 + 9x = 3 + 24 Combine like terms: -24 + 24 = 0 0 + 9x = 3 + 24 9x = 3 + 24 Combine like terms: 3 + 24 = 27 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| (m+4)(m-4)=0 | | (6p+4)(8p-3)=0 | | 4-y/8-2y | | x^3-8x^2+23x-22=0 | | 200000*X/3+150000*X=120000*X/3+90000*X+150000*X/3+150000*X+11000000+0.08*120000(500-X/3)+0.08*90000(500-X) | | e/15=5 | | (6n-7)(n-6)=0 | | 200000*(X/3)+150000*X=120000*(X/3)+90000*X+150000*(X/3)+150000*X+11000000+0.08*120000(500-X/3)+0.08*90000(500-X) | | (9x-25/8)-(7x+11/8) | | 2(5x+5)=8x+14 | | 200000*(X/3)+150000*X=120000*(X/3)+90000*X+150000*(X/3)+15*X+11000000+0.08*120000(500-X/3)+0.08*90000(500-X) | | (a+2)(5a+3)=0 | | (9x-31/8)-(7x+13/8) | | 0=-16t^2+52t+3 | | 7x1/10 | | 3(0)-2(5)=10 | | 4x^2-32x-25=0 | | x*log(x)-0.7*x+25=0 | | x*ln(x)-0.7*x+25=0 | | 1/2(41/2)-4=5 | | 1/2*2-4=5 | | 1/2*30-4=5 | | 3x-5=2x-8 | | 2x-8=3x-5 | | 200000*(X/3)+150000*X=120000*(X/3)+90000*X+15000*(X/3)+15*X+11000000+0.08*120000(500-X/3)+0.08*90000(500-X) | | 5(x+3)=x+27 | | 5+(-8)-4=29 | | 7x+27=x+3 | | x=20-2(7.5) | | 5+(-8)3=29 | | (1/3)*x=866 | | n/5=48 |